CuII and ZnII complexes with 1,3,4-thiadiazole-5-thiomethyl-based diamide - Zimmermann Londero, Ana Júlia; Abram, Ulrich; Roca Jungfer, Maximilian; Denise Schwade, Vânia (European journal of inorganic chemistry, 2025)
The diamide ligand, N,N’-bis(5-thiomethyl-1,3,4-thiadiazol-2-yl)-2,6-pyridinedicarboxamide (H2L) in its solvate form has two planar acetylamino groups, which are twisted slightly from the plane of the 5-thiomethyl-thiadiazole rings. The ligand reacts with: (i) copper(II) salts forming binuclear and pentanuclear compounds; (ii) zinc(II) acetate leading to an anionic trinuclear complex. The molecular structures of [Cu2(μ-H2O)(L)2] (1), [Cu5(dmf)(μ3-OH)2(L)3(Lb)]0.8[Cu5(μ3-OH)2(L)3(Lb)]0.2 ⋅ 0.5DMF⋅H2O (2) and [Zn(H2O)2(dmf)4][Zn3(μ3-OH)(L)3]2 ⋅ 2DMF ⋅ H2O (3) (where Lb2− represents the partially hydrolyzed ligand) were confirmed by X-ray diffractometry. We have found that compound 1 can exist as two tautomers: the aqua bridge in [Cu2(μ-H2O)(L)2] and the hydroxy bridge in [Cu2(μ-OH)(HL)(L)]. All compounds were characterized by elemental analysis and ESI mass spectrometry as well as FT-IR, Raman and UV-Vis spectroscopy. The luminescence properties of H2L⋅DMF and compound 3 were investigated. Compound 3 has strong fluorescence with the emission band centered at 508 nm, and fluorescence lifetime of 1.44 ns. The potential of chalcogen bonding interactions in aroylamidothiadiazoles and their compounds is discussed based on DFT calculations. The cis-ketone-configuration of oxygen and sulfur is energetically favored over other potential rota- and tautomers. Most importantly, the deprotonation of the ligand increases the O ⋅ ⋅ ⋅ S interaction strength due to a larger negative charge at oxygen leading to increased conformational stability in the coordination compounds. A massively increased delocalization of the nitrogen atoms lone pair in the deprotonated state compared to the protonated state, however, may be the main reason for the observed conformation.
Online veröffentlicht am 16. Februar 2025
Gesehen am 18.08.2025